2013
DOI: 10.1074/jbc.m113.480822
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Hypoxic Leukemia Cells Enhance Tube Formation in Endothelial Cells

Abstract: Background:We recently showed communication between leukemia and endothelial cells and induction of angiogenesis via exosomes. Results: Hypoxic leukemia cells secrete exosomal miRNA, which enhances tube formation in endothelial cells. Conclusion: Exosomal miRNA from a tumor itself helps modulate the microenvironment of the tumor. Significance: This study provides novel insight into the role of exosomes in cancer development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
277
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(287 citation statements)
references
References 36 publications
(48 reference statements)
8
277
1
1
Order By: Relevance
“…Our flow cytometry detection showed that hucMSC-Ex were also positive for CD29 (data not shown). The effects of hucMSC-Ex on proliferation, migration, and tube formation of endothelial cells together contribute to new vessel formation [21]. Furthermore, our previous studies proved that hucMSC-Ex could alleviate liver fibrosis [15], protects against acute kidney injury [16], and enhance cutaneous wound closure [29].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our flow cytometry detection showed that hucMSC-Ex were also positive for CD29 (data not shown). The effects of hucMSC-Ex on proliferation, migration, and tube formation of endothelial cells together contribute to new vessel formation [21]. Furthermore, our previous studies proved that hucMSC-Ex could alleviate liver fibrosis [15], protects against acute kidney injury [16], and enhance cutaneous wound closure [29].…”
Section: Discussionmentioning
confidence: 95%
“…Extracellular vesicles derived from human bone marrow mesenchymal stem cells could promote angiogenesis in tissue regeneration [17,18]. Exosomes enhance angiogenesis by delivering microRNAs, mRNAs, and active proteins [19][20][21][22][23][24]. We previously reported that exosomes from human umbilical cord mesenchymal stem cells (hucMSC-Ex) intensively enhance cutaneous wound healing; however, the effects of hucMSC-Ex on angiogenesis and the underlying mechanisms are not well characterized.…”
mentioning
confidence: 99%
“…Additionally, the involvement of vesicular miRNAs in neo-angiogenesis has been studied such as miRNA-210 that exhibited strong pro-angiogenic activity 22,40,83 . Furthermore, miRNA-210 has been observed to suppress the expression of specific genes such as EFNA3 (coding for Ephrin-A3) in endothelial cells, resulting in enhanced neo-angiogenesis 21,39,73 . Colorectal carcinoma cellsderived vesicular miRNA-9 shows pro-angiogenic effects through inhibiting the expression of suppressor of cytokine signaling 5 (SOCS 5), promoting the activation of the janus kinase/signal transducers and activators of transcription (JAK/STAT) signaling, a driver of endothelial cell migration 85 .…”
Section: Evs Set the Place And Time For Neo-angiogenesismentioning
confidence: 99%
“…Several studies demonstrate that small cellularly secreted vesicles called exosomes mediate much of MSCs' tissue healing capabilities [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. MSC derived exosomes are internalized by target cells and transfer proteins, RNA, lipids and metabolites [29].…”
Section: Phenotype Of Mscsmentioning
confidence: 99%